Bone loss in hepatitis B virus-infected patients can be associated with greater osteoclastic activity independently of the retroviral use - Dessordi, Renata [UNESP]; Watanabe, Ligia Moriguchi; Guimarães, Mariana Palma; Romão, Elen Almeida; de Lourdes Candolo Martinelli, Ana; de Carvalho Santana, Rodrigo; Navarro, Anderson Marliere (Springer Nature, 2021)
Nucleoside/nucleotide analogs such as tenofovir, have been used as long-term therapy for the treatment of hepatitis B and side effects such as the reduction in bone mineral density have been associated with their use. To determine the relationships between bone, hormonal, biochemical, and mineral parameters in patients with hepatitis B treated with nucleoside/nucleotide antiviral. A cross-sectional study was conducted with 81 adult patients with chronic hepatitis B infection. Dual-energy X-ray absorptiometry (DXA) was performed to assess bone mineral density. Biochemical analyses were performed for osteocalcin, deoxypyridinoline, parathyroid hormone, vitamin D, IGF-1, TSH, testosterone, estradiol, FSH, transaminases, urea, creatinine, calcium, serum and urinary phosphorus, magnesium, and FGF-23, body composition was performed by DXA. Participants, both gender, were divided according to the use of antiretrovirals: Group1: 27 inactive virus carriers without medication; Group2: 27 patients using tenofovir; and Group3: 27 patients using lamivudine or entecavir. DXA readings diagnosed osteopenia in the lumbar spine for 7.4% of individuals in Group1, 15% in Group2, and 3.7% in Group3. For all groups, we observed normal values in bone formation markers, osteocalcin levels as well as parathyroid hormone, insulin growth factor 1, and FGF-23. In all groups, we found increased levels of urinary deoxypyridinoline, a bone resorption marker. Increased levels in the bone resorption markers indicated a high resorptive activity of bone tissue. These data suggested high resorption activity of bone tissue in hepatitis B virus-infected patients independent of the use of antiretrovirals.